Aquatic aerobic exercise for children with cerebral palsy: a pilot intervention study. (February 2014) - Fragala-Pinkham, Maria A.; Smith, Hilary J.; Lombard, Kelly A.; Barlow, Carrie; O'Neil, Margaret E.
Abstract Purpose: The primary purpose of this pilot study was to evaluate the effectiveness of a14-week aquatic exercise program on gross motor function and walking endurance in children with cerebral palsy (CP). The secondary purpose was to evaluate changes in functional strength, aerobic capacity and balance. Method: A prospective time series group design consisting of four measurement sessions (two baseline, one post intervention, and 1-month follow-up) was used. Eight ambulatory children ages 6–15 years with CP and classified at Gross Motor Function Classification System Level I or Level III participated in an aquatic aerobic exercise program. Results: Significant improvements were observed for the primary outcomes of gross motor function and walking endurance. No significant differences between any of the secondary measures were observed, although all of the measures demonstrated trends of improvement after intervention. Conclusion: Ambulatory children with CP may improve their gross motor skills and walking endurance after an aquatic exercise program held twice per week for 14 weeks, utilizing moderate-to-vigorous exercise intensity and consisting of functional activities.